Aberrant skeletal muscle morphogenesis and myofiber differentiation characterize equine myotonic dystrophy - Stephanie J. Valberg; Zoë J. Williams; Elizabeth G. Ames; James R. Mickelson; Yvette S. Nout-Lomas; Gabriele Landolt; Macarena Sanz; Keri Gardner (PLoS ONE, 2026)
Equine myotonic dystrophy (eMD) is a rare neuromuscular disorder of undetermined origin marked by muscle hypertrophy and stiffness, dystrophic muscle histopathology, and myotonic discharges. In humans, myotonic dystrophy (DM) arises from trinucleotide repeat expansions in dystrophia myotonica protein kinase ( DMPK ) (DM1) or tetranucleotide expansions in cellular nucleic acid-binding protein ( CNBP ) (DM2), which disrupt mRNA processing and induce embryonic splicing patterns across multiple genes. In 6 eMD Quarter Horse types, (2–36 months-of-age) and 8 control Quarter Horses we determined: (1) fiber type composition of triceps , gluteal, and semimembranosus muscles; (2) differential gene (DEG) and protein (DEP) expression using transcriptomic and proteomic analyses; (3) presence of repeat expansions in transcripts of DMPK or CNBP and (4) exon 7 retention in CLCN1 or exon 22 splicing in ATP2A1 . Predominance and clustering of type 1 fibers, expression of embryonic myosin, and upregulated mitochondrial and sarcomeric DEPs characterized eMD hindlimb musculature. Gene ontology (GO) analysis of 730 upregulated DEGs identified numerous GO terms related to morphogenesis of mesoderm-derived tissues and upregulated genes impacting myoD expression in eMD muscle. Top upregulated DEG involved myogenesis ( MYOZ2, SBK2, SBK3, PAMR1 ), neurons, transcription/translation, cytoskeleton, basement/plasma membranes, and calcium binding/transport. Top upregulated proteins also impacted muscle morphogenesis (MUSTN1, CSRP3, TMSBX4, PDLIM, CALD1) as well as categories of mitochondria, sarcomere, extracellular matrix/ basement membrane, transcription, translation, cell cycle regulation, neurons amongst others. Downregulated DEP primarily impacted mitochondria, the sarcomere and glycogen metabolism. Notably, unlike human myotonic dystrophy, trinucleotide repeat expansions were not found in the DMPK 3’UTR (CTG) n nor tetranucleotide repeat expansions (CCTG) n in intron 1 of CNBP . Isoforms of CLCN1 containing fetal exon 7 were detected in equal frequency in eMD and control muscle and exon 22 was not alternatively spliced in ATP2A1 as has been found in DM1. Thus, distinct from DM1 and DM2, eMD is driven by unique molecular mechanisms impacting skeletal muscle morphogenesis, neurons and regulation of gene transcription/translation that alter fiber type composition, distribution and morphology. The origin of myotonia does not appear to be driven by a mutation in CLCN1 or retention of exon CLCN 7. Expanded splice site analysis and further research is warranted to elucidate the cause of myotonia and the distinct etiology of eMD.